Efektivitas Evaluasi Pendidikan Dan Pelatihan Kepemimpinan Tingkat IV - Fajar Iswahyudi (Puslatbang KHAN, 2017)
Evaluation leadership training level IV is an important instrument to ensure the achievement of learning objectives. For that evaluation is required to be effective. Effective evaluation carried out with 5 levels. However, leadership training Level IV Evaluation can not meet the evaluation mechanism 5 Level, if viewed from the type of evaluation are applied and time of the evaluation. For that we can conclude the evaluation of leadership training level IV not yet effective. Given the importance of evaluation leadership training level IV, the implementation of the evaluation can be prosecuted more effectively. Mechanism that can be used is the evaluation of Level 5 by modifying the type of evaluation and implementation time of evaluation.